Psychophysiological components of the activities of operators of nuclear power plants as a factor of accidents in the conditions of the threat of social catastrophe - Shevchenko, O.A.; Sheviakov , O.V.; Kornienko, V.V.; Burlakova, I.A.; Slavska , Y.A.; Zhyhaylo , N.I.; Vakulik , V.V.; Ostapenko, I.S.; Gerasimchuk, O.A.; Doroshenko, E.Y.; Prykhodko , V.V.; Chernihivska , S.A.; et al. (Medicni Perspektivi, 2023)
The purpose of the study is to establish the peculiarities of operator’s work and the leading factors of the formation of its psychophysiological tension at nuclear power plants in the conditions of the threat of social catastrophe in connection with military operations. The study was conducted at the Zaporizhzhya and Khmelnytsky nuclear power plants for the period of 2020-2021. To study the dynamics of the psychophysiological state of operators of nuclear power plants, a verbal-communicative diagnostic method was used to collect information about the operators investigated using Google Form and traditional physiological, psychological and psychophysiological methods. The socio-demographic features of the investigated operators of the block control panel were analyzed. It was established that men only (100%) aged 24-49 and with work experience from 4 to 20 years were among the examined. All surveyed operators (41 people) are residents of the city, with completed higher education and are family members. The methods of psychological (reactive anxiety, mood, activity, mood, attention), physiological (cardiography, blood pressure) and psychophysiological (simple sensorimotor and psychophysical) research methods were used to empirically assess the intensity of activity of the operators of the block control panel of nuclear power plants. There were examined operators, while on duty when control errors and pre-accident situations were recorded. It was established that the psychological, physiological and psychophysiological characteristics of these operators are followed by increased reactive anxiety, decreased indicators of well-being, activity, mood, reduction in functional reserves of the cardiorespiratory system, mental and physical capacity. These indicators are considered as criteria for the development of regulatory measures. It is proposed to take into account not only technological factors, but also the psychophysiological features of operators in the dynamics of their manifestation when developing measures for the optimal selection and personnel placement. The complex of methods for researching the functional state of operators can be used to optimize their professional selection and retraining, which can lead to reducing accidents and costs for professional training. The expected effect is an increase in the efficiency and quality of operator’s activity, the productivity and reliability of the performance of production tasks, an increase in professional longevity, a decrease in rate and occupationally-related morbidity of these specialists.